Emo : How Fans Defined a Subculture - Burek Pierce, Jennifer (Book collections on Project MUSE., 2020)
""Nerdfighteria," a first-of-its-kind online literary community with nearly three million members, is the brainchild of brothers Hank and John Green. From their YouTube channel, the brothers provide video clips from John, a best-selling author most famous for his Young Adult book, "The Fault in Our Stars." These clips not only give fans personal insights into his works, they also provide unique access to the author, inspiring fans to create their own fan art. Looking closely at this new way of discussing books and creating fan art, Jennifer Burek Pierce not only sheds new light on this online community of literary fans, she also reveals what it tells us about the changing nature of reading in the digital age. Among the questions she asks are: Why do scholars regard some individuals as fans rather than readers? What is the difference between communities of readers, participatory culture, and fandoms? What creates bonds between authors and readers, or among readers themselves, and how do they talk about their often digital connections? Ultimately, she finds that the enduring public discourse that comprises Nerdfighteria provides a nuanced consideration of contemporary readers and of online fandom more broadly. The result is a fascinating examination that should appeal to fan and media studies scholars alike, as well as fans of the Green brothers, and historians of the book"--